Question 1:
<h3>Answer: The number does <u>not</u> change</h3>
Removing the zero from 0.76 leads to .76 which is the same as before. Both lead to
in scientific notation.
Personally I prefer the zero up front to make the decimal point stand out easier. Of course it's just a preference, so its up to you to decide which you prefer.
===========================================
Question 2:
<h3>Answer: Yes the number changes</h3>
Taking the zero out of 10.25 leads to 1.25 which is definitely a different number (and smaller). Therefore, this zero is a significant digit compared to before.
Let,
f(x) = -2x+34
g(x) = (-x/3) - 10
h(x) = -|3x|
k(x) = (x-2)^2
This is a trial and error type of problem (aka "guess and check"). There are 24 combinations to try out for each problem, so it might take a while. It turns out that
g(h(k(f(15)))) = -6
f(k(g(h(8)))) = 2
So the order for part A should be: f, k, h, g
The order for part B should be: h, g, k f
note how I'm working from the right and moving left (working inside and moving out).
Here's proof of both claims
-----------------------------------------
Proof of Claim 1:
f(x) = -2x+34
f(15) = -2(15)+34
f(15) = 4
-----------------
k(x) = (x-2)^2
k(f(15)) = (f(15)-2)^2
k(f(15)) = (4-2)^2
k(f(15)) = 4
-----------------
h(x) = -|3x|
h(k(f(15))) = -|3*k(f(15))|
h(k(f(15))) = -|3*4|
h(k(f(15))) = -12
-----------------
g(x) = (-x/3) - 10
g(h(k(f(15))) ) = (-h(k(f(15))) /3) - 10
g(h(k(f(15))) ) = (-(-12) /3) - 10
g(h(k(f(15))) ) = -6
-----------------------------------------
Proof of Claim 2:
h(x) = -|3x|
h(8) = -|3*8|
h(8) = -24
---------------
g(x) = (-x/3) - 10
g(h(8)) = (-h(8)/3) - 10
g(h(8)) = (-(-24)/3) - 10
g(h(8)) = -2
---------------
k(x) = (x-2)^2
k(g(h(8))) = (g(h(8))-2)^2
k(g(h(8))) = (-2-2)^2
k(g(h(8))) = 16
---------------
f(x) = -2x+34
f(k(g(h(8))) ) = -2*(k(g(h(8))) )+34
f(k(g(h(8))) ) = -2*(16)+34
f(k(g(h(8))) ) = 2
Answer:
The independent is the 90 gallons and the dependent is the 8 minutes.
Hope this helps!
Step-by-step explanation:
Answer:
m=-1/6
Step-by-step explanation:
The slope equation is m=(y₂-y₁)/(x₂-x₁)
For this problem
y₂=-5
y₁=0
X₂=32
x₁=2
Then applying the equation
m=(-5-0)/(32-2)
m=(-5)/(30)
m=-1/6
m=-0,167
The negative means the slope is decreasing
Answer:
9a-13b
Step-by-step explanation:
6a-12b+3a-b
=6a+3a-12b-b
=9a-13b